The Impact of Synbiotics on the Bacterial Flora During the Course of Chronic Sinusitis - Karolina Goroszkiewicz; Grażyna Lisowska; Grażyna Stryjewska-Makuch; Olga Karłowska-Bijak; Maciej Misiołek (Medicina)
Background and objectives: Chronic rhinosinusitis (CRS) is a multifactorial inflammatory condition often associated with microbiome imbalance (dysbiosis). Recent studies highlight the potential role of synbiotics—combinations of probiotics and prebiotics—in modulating the microbiota and supporting immune responses. The authors of this study aimed to evaluate the impact of oral synbiotic supplementation on the sinus microbiota in patients undergoing endoscopic sinus surgery (ESS) for CRS. Materials and Methods: A total of 425 adult patients with CRS were enrolled in a multicenter retrospective study. According to EPOS 2020 guidelines, participants qualified for ESS. The intervention group (n = 194) received a synbiotic preparation for 6–8 weeks before and after surgery; the control group (n = 231) received no supplementation. Intraoperative and follow-up bacteriological samples were collected and analyzed. Statistical analysis included chi-square, t-tests, Wilcoxon tests, and ANOVA models. Results: Patients receiving synbiotics showed a significant reduction in pathogenic bacterial colonies postoperatively compared to the control group. In the synbiotic group coagulase-negative staphylococci appeared more frequently. Patients in the synbiotic group required significantly less postoperative antibiotic therapy (p < 0.05). Both groups exhibited an increase in Gram-positive and physiological flora and a decrease in Gram-negative bacteria following ESS. Conclusions: Synbiotic supplementation may beneficially influence the composition of the sinus microbiota and reduce pathogenic bacterial colonization following ESS. The findings suggest that synbiotics could serve as a supportive strategy in CRS treatment, potentially decreasing the need for postoperative antibiotics.